2020
DOI: 10.3389/fpsyg.2020.00607
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Blood Pressure on Cognitive Performance. An 8-Year Follow-Up of the Tromsø Study, Comprising People Aged 45–74 Years

Abstract: Background: The relationship between blood pressure (BP) and cognition is complex were age appears to be an intervening variable. High and low BP have been associated with cognitive deficits as part of the aging process, but more studies are needed, especially in more recent birth cohorts. Methods:The study sample comprised 4,465 participants, with BP measured at baseline in the Tromsø Study, Wave 6 in 2007-2008 (T0), and cognition assessed at follow-up 8 years later, in 2015-2016 in Tromsø Study 7 (T1). Age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 49 publications
0
25
0
1
Order By: Relevance
“…The cognitive domains that are negatively affected by hypertension include abstract reasoning and/or executive function , memory and mental processing speed 3 . A study that used the Digit Symbol Substitution Test , which is a more sensitive measure of cognitive impairment than the Mini-Mental State Examination (MMSE), showed that in men aged 45–55 years, higher SBP and DBP were significantly associated with lower cognitive performance at 8 years of follow-up 25 . In women, higher SBP was associated with better cognition at younger ages and poorer cognition at older ages.…”
Section: Epidemiologymentioning
confidence: 99%
“…The cognitive domains that are negatively affected by hypertension include abstract reasoning and/or executive function , memory and mental processing speed 3 . A study that used the Digit Symbol Substitution Test , which is a more sensitive measure of cognitive impairment than the Mini-Mental State Examination (MMSE), showed that in men aged 45–55 years, higher SBP and DBP were significantly associated with lower cognitive performance at 8 years of follow-up 25 . In women, higher SBP was associated with better cognition at younger ages and poorer cognition at older ages.…”
Section: Epidemiologymentioning
confidence: 99%
“…It is more likely that the tendency for decline in SBP closer to death in men can be related to differences in cardio‐vascular differences between the sexes. It has for a long time been known that men have a lower survival rate than females after a diagnosis of dementia (Rizzuto et al, 2012) and there are differences in blood pressure development, cardio vascular disease, and myocardial incident of infarction between the sexes as they age (Albrektsen et al, 2016; Barrett‐Connor, 2013; Hestad, Engedal, Schirmer, et al, 2020). It is seen that there is an accelerated risk of myocardial infarction in young men compared to young women.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that blood pressure drops as people approach death (Delgado et al, 2018; Goodwin, 2018; Hestad et al, 2020). Delgado et al, among others, have demonstrated in people over the age of 60 that blood pressure begins a downward trajectory more than 10 years before death, with the steepest declines occurring 2 years prior to death (Delgado et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found an interaction between age and sex for SBP at younger ages, in that women start out with a lower pressure but end up with a higher blood pressure than men. It is seen from population studies that men and women show differential developmental trajectories regarding BP regulations over a lifetime ( Joyner et al, 2016 ; Hestad et al, 2020 ). In the present study there were significant differences between men and women in blood pressure development.…”
Section: Discussionmentioning
confidence: 99%